Experimental Investigation on Thermal Performance of CPU cooled by Nanofluids - Aziz N.M.S.B.N.A.; Gunnasegaran P.; Mukhtar A.B. (American Institute of Physics, 2025)
The increasing demand for high-performance computing necessitates efficient cooling of central processing units (CPUs) to ensure optimal functionality and prevent overheating. Nanofluids, colloidal suspensions comprising scattered nanoparticles in a base fluid, have emerged as a promising solution due to their distinct thermal properties and potential for enhanced heat transfer. Thus, the main objective of the current study is to evaluate the thermal performance and efficacy of nanofluids as coolants for desktop PC CPU cooling system. To achieve this, an extensive experimental setup was devised to analyze the heat transfer characteristics of nanofluids under diverse operating conditions. Different types of deionized water based-nanofluids, which are Al2O3, CuO and Fe2NiO4 with nanoparticle mass concentration of 0.3% were blended for 3 hours using magnetic stirrer and followed by 6 hours of ultrasonic bath at a constant temperature of 50?. The stability of the prepared nanofluid will be monitored and enhanced through this method of preparation. The thermal performance of desktop PC CPU is evaluated based on the highest operating temperature of the processors under the maximum load of computer usage. For performance comparison, a conventional coolant deionized water was utilized as a reference. Among all the nanofluids used, Fe2NiO4-H2O demonstrates the most efficient cooling performance. Its temperature gradually decreases from the peak value to 45C under the same operating conditions with other type of nanofluids used. This significant temperature reduction can be linked to the superior thermal conductivity of Fe2NiO4 nanoparticle. This finding underscores the potential of nanofluids as an advanced cooling solution for desktop PC CPU system. ? 2024 American Institute of Physics Inc.. All rights reserved.